Reply to "Comment on 'Free-free opacity in warm-dense aluminum' - Vinko, S; Gregori, G; Wark, J (2011)
We reply to the comment by Iglesias [HEDP, XXX] regarding our implementation of a solid-state pseudopotential in a model for the calculation of the free--free opacity in warm-dense aluminum [HEDP 5(2009), 124-131]. Some further details are given describing the method used to determine the adjustable parameter in the pseudopotential and several important limitations are discussed. © 2010 Elsevier B.V.